Dihydrogen complexes of rhodium: [RhH2(H2)x (PR3)2]+ (R = Cy, iPr; x = 1, 2). - Ingleson, M; Brayshaw, S; Mahon, M; Ruggiero, G; Weller, A (2005)
Addition of H2 (4 atm at 298 K) to [Rh(nbd)(PR3)2][BAr(F)4] [R = Cy, iPr] affords Rh(III) dihydride/dihydrogen complexes. For R = Cy, complex 1a results, which has been shown by low-temperature NMR experiments to be the bis-dihydrogen/bis-hydride complex [Rh(H)2(eta2-H2)2(PCy3)2][BAr(F)4]. An X-ray diffraction study on 1a confirmed the {Rh(PCy3)2} core structure, but due to a poor data set, the hydrogen ligands were not located. DFT calculations at the B3LYP/DZVP level support the formulation as a Rh(III) dihydride/dihydrogen complex with cis hydride ligands. For R = iPr, the equivalent species, [Rh(H)2(eta2-H2)2(P iPr3)2][BAr(F)4] 2a, is formed, along with another complex that was spectroscopically identified as the mono-dihydrogen, bis-hydride solvent complex [Rh(H)2(eta2-H2)(CD2Cl2)(P iPr3)2][BAr(F)4] 2b. The analogous complex with PCy3 ligands, [Rh(H)2(eta2-H2)(CD2Cl2)(PCy3)2][BAr(F)4] 1b, can be observed by reducing the H2 pressure to 2 atm (at 298 K). Under vacuum, the dihydrogen ligands are lost in these complexes to form the spectroscopically characterized species, tentatively identified as the bis hydrides [Rh(H)2(L)2(PR3)2][BAr(F)4] (1c R = Cy; 2c R = iPr; L = CD2Cl2 or agostic interaction). Exposure of 1c or 2c to a H2 atmosphere regenerates the dihydrogen/bis-hydride complexes, while adding acetonitrile affords the bis-hydride MeCN adduct complexes [Rh(H)2(NCMe)2(PR3)2][BAr(F)4]. The dihydrogen complexes lose [HPR3][BAr(F)4] at or just above ambient temperature, suggested to be by heterolytic splitting of coordinated H2, to ultimately afford the dicationic cluster compounds of the type [Rh6(PR3)6(mu-H)12][BAr(F)4]2 in moderate yield.